Aceh in Three Phases: Genealogies of Modernism, Islamism, and Ethnonationalism - M. Alkaf; Muhammad Said; Shafrida Wati; Noorsafuan Che Noh; Saiful Hakam (Fakultas Syariah IAIN Langsa, 2026)
Ideally, the development of Islamic modernism, Islamism, and ethnonationalism in Aceh should be understood as interconnected historical processes that collectively shaped the Acehnese people's collective identity. However, previous studies have generally examined these three intellectual currents separately, focusing primarily on political events while failing to explain the genealogical relationships among them. This study aims to analyze the development of Islamic modernism, Islamism, and ethnonationalism in Aceh, identify the factors underlying their emergence, and explain their implications for the religious, social, and political life of Acehnese society. This research employs a qualitative library research design using historical methods and genealogical analysis of both primary and secondary sources. The findings reveal that Islamic modernism laid the foundation for the reform of Islamic education and thought, Islamism developed as an articulation of the relationship between Islam and the state within the framework of the Republic of Indonesia, while ethnonationalism emerged in response to changes in the political relationship between Aceh and the central government. These three intellectual currents evolved continuously and collectively shaped Aceh's socio-political identity through the era of special autonomy.